Risk factors associated with MDR-TB at the onset of therapy among new cases registered with the RNTCP in Mumbai, India - Sachin R Atre; Desiree T. B. D'Souza; Tina S Vira; Anirvan Chatterjee; Nerges F Mistry (Wolters Kluwer Medknow Publications, 2011)
Background: Multidrug - resistant TB (MDR - TB) has emerged as a major threat to global TB control efforts in recent years. Facilities for its diagnosis and treatment are limited in many high - burden countries, including India. In hyper - endemic areas like Mumbai, screening for newly diagnosed cases at a higher risk of acquiring MDR - TB is necessary, for initiating appropriate and timely treatment, to prevent its further spread. Objective: To assess risk factors associated with MDR - TB among Category I, new sputum smear-positive cases, at the onset of therapy. Materials and Methods: The study applied an unmatched case - control design for 514 patients (106 cases with MDR - TB strains and 408 controls with non - MDR - TB strains). The patients were registered with the Revised National Tuberculosis Control Program (RNTCP) in four selected wards of Mumbai during April 2004 - January 2007. Data were collected through semi - structured interviews and drug susceptibility test results. Results: Multivariate analysis indicated that infection with the Beijing strain (OR = 3.06; 95% C.I. = 1.12 - 8.38; P = 0.029) and female gender (OR = 1.68; 95% C.I. = 1.02 - 2.87; P = 0.042) were significant predictors of MDR-TB at the onset of therapy. Conclusion: The study provides a starting point to further examine the usefulness of these risk factors as screening tools in identifying individuals with MDR-TB, in settings where diagnostic and treatment facilities for MDR-TB are limited.